Економічні інструменти у сфері виробництва в праві Європейського Союзу - Качурінер, Вікторія Львівна; Качурінер, В. Л. (My University, 2019)
Стаття присвячена правовому регулюванню екологічної політики Європейського Союзу у сфері виробництва за допомогою економічних інструментів. Розглянуто екологічне законодавство Європейського Союзу у сфері виробництва, яке характеризується розширенням правових вимог щодо охорони навколишнього середовища в діяльності промислових підприємств із застосуванням безпечних технологій та превентивних заходів в їх функціонуванні, з обов’язковим проведенням екологічної експертизи й оцінки впливу на навколишнє середовище.

The article is dedicated to legal regulation of the environmental policy of the European Union in the sphere of production. The author consider environmental legislation of the European Union in the sphere of production that is characterized by the extension of legal requirements for environmental protection in industrial activities with the use of safe technologies and preventive measures in their operation, with mandatory environmental impact assessments and assessment of impacts on the environment. The author selects such economic instruments as the European Registry of Emissions, the environmental tax, the LIFE program. The importance of these tools is provided through public access to environmental information. On the consumer side – information for consumers (eco-labeling, information centers, product profiles), indirect taxation, deposit schemes and their payments. The use of economic instruments helps to make tools such as voluntary agreements, environmental labeling, environmental management and environmental auditing more relevant to the public and EU Member States. The possibility of emerging risks in the field of production makes it possible to use such economic instruments as taxes and duties. Further study of this aspect of European policy can help to improve existing and develop new, more effective ways to achieve environmental goals through the use of fiscal instruments. Using the experience of EU countries in applying tax levers of environmental policy is also important for the implementation of the European integration policy of our country. Key words: European Union, environmental protection, production, economic
Качурінер В. Л. Економічні інструменти у сфері виробництва в праві Європейського Союзу / В. Л. Качурінер // Юридичний науковий електронний журнал. - 2019, № 2. - С. 274-277.
Keywords: Європейський Союз; сфера виробництва; економічні інструменти; податки і мита; програма LIFE; European Union; environmental protection; production; economic instruments; taxes and duties; LIFE-program; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES